Extrinsic labelling of zinc and calcium in bread - Fredlund, Kerstin; Rossander-Hulthén, Lena; Isaksson, Mats; Almgren, Annette; Sandberg, Ann-Sofie (Applied radiation and isotopes, 2002)
This study investigated the effect of different means of extrinsic administration of 65Zn and 47Ca in white wheat flour bread on the measured absorption. Eight healthy subjects were served 80 g of labelled bread as a standardized breakfast after an overnight fast on three occasions. Extrinsic labelling of the meals with 65Zn and 47Ca was done in three ways: ( a) by adding the isotopes to the bread 16 h before it was served, ( b) by adding the isotopes shortly before serving or ( c) by adding the isotopes to the water used in dough making. Zinc and calcium chloride corresponding to 3.2 mg (49 μmol) zinc and 275 mg (6.9 mmol) calcium in one portion were added to the dough. Whole-body retention was measured by whole-body counting. The fractional absorption of zinc was ( a) 0.243±0.122, ( b) 0.217±0.101 and ( c) 0.178±0.063 (mean±SD), and the fractional absorption of calcium (expressed as calcium retention on day 7) was ( a) 0.351±0.108, ( b) 0.357±0.131 and ( c) 0.334±0.117 (mean±SD). No significant difference ( p>0.05) was seen between the different ways for either zinc nor calcium.